1987
DOI: 10.1109/joe.1987.1145232
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Signal and Noise Field Estimation Using the<tex>L</tex>1 (Least Absolute Values) Norm

Abstract: Abstmct-In this paper a new method for obtaining a quantitative estimate of an acoustic field consisting of a set of discrete sources and background noise is described. The method is based on the L1 (least absolute values) norm solution to an underdetermined system of linear equations defining the Fourier transform of the signal series. Implementations of the method with either equality or inequality constraints are presented and discussed. The much faster and more compact equality constraint version with a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…Using Lemma 4 and the matrix norm , we have that Now (31) proving the first inequality. To prove the second one we first note that by the singular value decomposition of , we have (32) where in the last inequality we used (31). In [46] it is shown that where and .…”
Section: Appendix IV Proof Of Theoremmentioning
confidence: 85%
See 1 more Smart Citation
“…Using Lemma 4 and the matrix norm , we have that Now (31) proving the first inequality. To prove the second one we first note that by the singular value decomposition of , we have (32) where in the last inequality we used (31). In [46] it is shown that where and .…”
Section: Appendix IV Proof Of Theoremmentioning
confidence: 85%
“…Typically problems are solved by replacing the original continuous problem by a discrete one, and then using linear programming techniques [27], [30], [31]. Discretization techniques are also common for solving the corresponding and measures [32].…”
Section: A Characterization Of the Optimal Filtermentioning
confidence: 99%
“…This LAD problem is formulated as (3) Using Proposition 1, we turn the problem described in (3) into another form, which is easier to solve.…”
Section: A Theories Of An Nn Of the Lad With Equality Constraintsmentioning
confidence: 99%
“…The LAD estimation approach has been used in signal processing [4], image restoration [32], and blind source separation [36]. In this section, we apply the proposed cooperative recurrent neural networks (CRNNs) to parameter estimation of system identification under a class of non-Gaussian noise environments.…”
Section: Application To Parameter Estimationmentioning
confidence: 99%